Analisis Kelebihan dan Kekurangan Penggunaan ChatGPT Dalam Pembelajaran - Diana Riyanti; Sarah Wulandari; Iin Nurjanah; Adi Saputra; Basinun Basinun (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2026)
The use of ChatGPT in learning has become an increasingly popular trend, but it has also raised concerns about its impact on the quality of learning. This study aims to analyze the advantages and disadvantages of using ChatGPT in learning. This analysis was conducted by examining ChatGPT's capabilities in processing information, creating content, and assisting students in learning. This study used a qualitative approach with a case study method to analyze the advantages and disadvantages of using ChatGPT in learning. Data were collected through questionnaires and semi-structured interviews with lecturers and students who used ChatGPT. The analysis results show that ChatGPT has advantages in processing information quickly and accurately, but also has disadvantages in producing inaccurate information and reducing students' critical thinking skills. This study recommends the wise and balanced use of ChatGPT in learning, as well as the development of more effective and efficient learning strategies utilizing this technology.